Vastus intermedius vs vastus lateralis fascicle behaviors during maximal concentric and eccentric contractions - Ando, R.; Nosaka, K.; Tomita, A.; Watanabe, K.; Blazevich, A. J.; Akima, H. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Vastus intermedius (VI) plays a major role in knee extension, but its fascicle behaviors during dynamic contractions are not well understood. This study aimed to compare VI and vastus lateralis (VL) fascicle behaviors during singular maximal concentric and eccentric contractions. Thirteen men (27.1 ± 3.4 years) performed maximal isokinetic concentric contractions through knee joint angles of 105° to 35° (0° = full extension) and eccentric contractions from 35° to 105° at an angular velocity of 30°/s. Longitudinal VI and VL sonographic images were simultaneously recorded at 30 Hz, and muscle fascicle lengths at the knee joint angles of 40° and 100° were measured to compare the magnitudes of fascicle length change between the muscles. During concentric contractions, VI and VL fascicle lengths at 100° were 108 ± 12 mm and 104 ± 12 mm, respectively, and shortened by 36 ± 12 mm for VI and 28 ± 13 mm for VL (not statistically different; P = .13) at 40°. During eccentric contractions, VI and VL fascicle lengths at 40° were 72 ± 7 mm and 75 ± 8 mm, respectively, but lengthened by 35 ± 9 mm for VI and 24 ± 5 mm for VL at 100°, with a significant difference between the muscles (P = .01). These results indicate that VI fascicles are lengthened 1.4 times more than VL fascicles during eccentric contractions, whereas VI and VL fascicles shorten similarly during concentric contractions. This suggests a possibility that a greater mechanical strain is imposed to VI than VL during eccentric contractions.